Designing Intelligent Mechanical Ventilator and User Interface Using LabVIEW® - Guler, Hasan; Turkoglu, Ibrahim; Ata, Fikret (Springer Heidelberg, 2014)
The main purpose of this paper is to design mechanical ventilator and to develop user interface. Mechanical ventilators have been generally controlled by open-loop controller. Thus, workload of clinicians in intensive care unit is too much. In this study, an intelligent mechanical ventilator was designed as a closed loop to reduce workload of clinicians. The device is called intelligent ventilator because of using an intelligent control technique, fuzzy logic. A software-based interface was developed in LabVIEW(A (R)) to monitor and adjust respiratory variables. In this work, fuzzy controlled the inspiration/expiration valves and pressure regulator in ventilator. Fuzzy has two inputs and two outputs for inspiration/expiration times and it has one input and one output for pressure regulator. The performance of device was tested with eight female Wistar albino rats using pressure-controlled ventilation. Student t test for p < 0.05 was applied to the calculated rats' lung parameters to determine statistical discrepancy. The results show that there is no statistical discrepancy in rats' lung parameters for before and after the experiments. It can be said that the designed ventilator supports rats' artificial respiration, successfully and does not alter the lung parameters of rats.
Keywords: Fuzzy logic; Medical control system; Respiration; LabVIEW